A Study on Issues and Challenges Faced by Women Researchers (International Journal of Innovative Research in Engineering & Management, 2022)
Women are going ahead in all the fields  from kitchen to space. They are establishing their mark  wherever they go and are paving way for many others to join.  But still many women are not able to enter into the field of  research. Women are encountering many problems during  their journey to become a researcher from all dimensions.  Thus this study focused on identifying the issues and  challenges of women during their research activities and  observed that lack of financial resources and lack of facilities  are the main problems hindering their growth.
Keywords: Women Researchers; Issues of Women researchers; Henry Garrett Ranking